Pelatihan Metode Braille Untuk Meningkatkan Kemampuan Membaca dan Menghafal Al-Qur’an Bagi Penyandang Disabilitas (Tunanetra) di Pesantren Sam’an Darushudur Cimeunyan Bandung - Muhyi, Asep Abdul; Mimbar, Asep Saeful; Mud’is, Maulana Hasan (Civiliza Publishing, 2024)
Training and mentoring in the use of Braille Quran at Sam'an Darushudur Islamic Boarding School plays an important role in helping blind people read and memorize the Quran. This program focuses on educating blind students about the benefits of the Braille method, involvement in planning, training, and evaluation of skills. The methods used include counseling, training, and guidance so that students can understand, read, and practice the Quran correctly. Data collection was carried out through field research, literature, documentation, and interviews. The implementation stages start from identifying needs, planning, implementation, to operational mentoring. This program has succeeded in integrating the Braille method as an effective way to read the Quran in Islamic boarding schools, as seen from the success of blind students in learning quickly and improving their touch skills. Positive impacts include the ability of students to read the Quran using Braille more quickly. Recommendations include increasing infrastructure accessibility, active involvement of the academic community, and ensuring the sustainability of the program financially and managerially. This program is expected to be an inspiration for the development of similar programs in Islamic boarding schools, schools, or other foundations, so that it has a positive impact on the blind in learning and practicing the Qur'an.